2015
DOI: 10.1007/s00339-015-9321-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electron field emission from CuO nanoplate arrays decorated with Au nanoparticles

Abstract: A simple and controllable method was reported for the decoration of CuO nanoplate arrays with Au nanoparticles. It had been achieved through the reaction between Sn 2? and AuCl 4 -in the presence of CuO nanoplate arrays. The structure and electron field emission properties of CuO nanoplate arrays decorated with different amounts of Au nanoparticles were investigated. The results demonstrated a remarkable enhancement of field emission performance of CuO nanoplate arrays decorated with Au nanoparticles. The effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
(30 reference statements)
1
9
0
Order By: Relevance
“…In order to enhance the eld emission properties, the researchers employed various approaches to obtain surface modied, 18,19 hybrid, 20,21 and post-processed 22,23 CuO nanostructures. Recently, noble metal nanoparticles, such as Ag 18 and Au, 24 are decorated on the 1D CuO nanostructures by wet chemistry and enhanced eld emissions have been obtained due to the increased conductivity and improved semiconductor characteristics. Carbon materials (graphene oxide layers 19 and carbon nanotube network lms 25 ) and metal oxides such as ZnO nanoparticles 26 are also chosen to coat on the CuO nanostructures to improve the eld emissions.…”
Section: Introductionmentioning
confidence: 99%
“…In order to enhance the eld emission properties, the researchers employed various approaches to obtain surface modied, 18,19 hybrid, 20,21 and post-processed 22,23 CuO nanostructures. Recently, noble metal nanoparticles, such as Ag 18 and Au, 24 are decorated on the 1D CuO nanostructures by wet chemistry and enhanced eld emissions have been obtained due to the increased conductivity and improved semiconductor characteristics. Carbon materials (graphene oxide layers 19 and carbon nanotube network lms 25 ) and metal oxides such as ZnO nanoparticles 26 are also chosen to coat on the CuO nanostructures to improve the eld emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, decoration of Au nanoparticles for 24 hr along the textural boundaries of ZnO nanowires yields a larger emission current density of 2.1 mA/cm 2 at a lower applied field of 1.92 V/μm. Moreover, emission current density (i. e., 2.1 mA/cm 2 ) achieved from Au@ZnO nanowires (≡ Au/ZnO/ITO) at lower applied field (i. e., 1.92 V/μm) is relatively higher than the values reported for Ag/GO/ZnO composites, CNT‐ZnO composites, ZnO nanowire/CNT heterojunction, pristine ZnO nanopillers, metal particle decorated ZnO nanorods, Au decorated ZnO nanowires/nanopillers,, and CuO nanoplates, and pristine and MoS 2 decorated β ‐TiO 2 ranorods ,. The E on of ZnO/ITO (i. e., E on = 1.56 V/μm) required to acquire current density of 10 μA/cm 2 is reduced considerably after the controlled decoration of various amounts of Au nanoparticles.…”
Section: Resultsmentioning
confidence: 65%
“…mentioned above ,,. The E on observed for Au@ZnO nanowires hetero‐architectures after decoration of Au nanoparticles for 24 hr is reasonably lower than that reported for Ag and Graphene oxide decorated ZnO nanowire array (i. e., 1.4 V/μm), ZnO nanowire/CNT heterojunction (i. e., 1.5 V/μm at current density of 1 μA/cm 2 ), nitrogen implanted ZnO nanowires (i. e., 2.4 V/μm at current density of 0.1 μA/cm 2 ), Ag and Pt decorated ZnO nanorods (i. e., 1.9 and 2.6 V/μm, respectively), and Au decorated CuO nanoplates (i. e., 6.7 V/μm) . The non‐uniform and limited distribution of Au nanoparticles over the ZnO nanowires restricted the E on to 2 V/μm (defined at 1 μA/cm 2 ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Li et al demonstrated that decorated Au nanoparticles enhanced the¯eld emission performance of CuO nanoplate arrays. 15 Juan et al found that hydrogen annealing could improve thē eld emission properties of CuO nanowires. 16 For the in°uence of light illumination, Chen et al observed visible light illumination could enhance¯eld emission performance of CuO nanobelt arrays.…”
Section: Introductionmentioning
confidence: 99%